Hubungan Motivasi Berprestasi Dengan Hasil belajar Mata Kuliah Askeb V Pada Mahasiswa - Nasution, Ayannur; Rangkuti, Nur Aliyah (Jurnal Kesehatan Ilmiah Aufa Royhan, 2019)
Motivation is an energy change in a person that is characterized by the emergence of affective to achieve goals. The research design used was analytic survey with cross sectional approach. The population in this study were all semester VI students, amounting to 113 people with a sample population of 88 respondents. The sampling technique in this study is Stratified proportional random sampling where the number of class A and B samples is taken randomly. From the Chi-square statistical test results at a 95% confidence level with α = 0.05, obtained (α = 0,000). Of the 36 students who had sufficient achievement motivation in the Askeb V course the majority received a B grade of 19 students (21.6%). And of the 42 students who had less achievement motivation in the Askeb V subject, the majority received a C grade of 37 students (42%). There is a relationship of achievement motivation with the learning outcomes of Askeb V subject in semester VI students at the Darmais Padangsidimpuan Midwifery Academy in 2018. It is expected that students will develop motivation in themselves and also the lecturers to make students more enthusiastic and motivated to learn so that they get the learning outcomes maximum as expected.